Effects of chelating agents on the sol-gel synthesis of nano-zirconia: Comparison of the Pechini and sugar-based methods - Kazemi, Faramarz; Arianpour, Farzin; Taheri, Mahdiar; Saberi, Ali; Rezaie, Hamid Reza (Springer Science and Business Media LLC, 2020)
This study focused on the comparison of the Pechini and sugar-based combustion synthesis methods to produce nano-zirconia. Zirconium hydroxide was utilized as metal precursor and citric acid, sucrose, and fructose were used as chelating agents, followed by calcination at 500, 600, and 700°C in air, respectively. Characterization was conducted by thermal analysis, specific surface area measurement, Fourier transform infrared spectroscopy, X-ray diffraction, and scanning and transmission electron microscopy. When sucrose and citric acid were used as chelating agents during synthesis, mixtures of monoclinic and tetragonal phases were formed after calcination at 600 and 700°C. In the fructose samples, the tetragonal structure was the unique characterized phase. The tetragonal parameters in the fructose samples were determined using the diffraction data and the lattice parameter ratio was proven to increase with the temperature increase. Compared with the citrate and sucrose samples, the largest specific surface area (27 m2·g−1) and smallest particle size (39.1 nm) were obtained for the fructose sample after calcination at 700°C. The study revealed the formation of single-phase stabilized tetragonal zirconia using fructose as chelating agent after calcination at 500°C, and the presence and formation mechanism of stabilized tetragonal phase were also discussed on the basis of the X-ray and electron diffraction studies.